Investigation into techniques to isolate and develop human germ cells in vitro - Papadopoulou, E (2020)
Premature ovarian insufficiency (POI) occurs in 1% of women younger than 40 years of age. The manifestation of this condition varies considerably ranging from ovaries devoid of follicles (afollicular POI) to ovaries containing follicles at various stages of development (follicular POI). No methods exist in mainstream healthcare to restore ovarian function for POI patients and ≥70% of POI cases are idiopathic. The Reaggregated Ovary (RO) method, as established for mice, enables investigation into the developmental potential of oocytes by replacing dysfunctional ovarian cells. This approach could enable us to develop a potential treatment for patients with follicular POI. Investigations carried out in this thesis led to the establishment of key processes required to adapt the RO method for human tissue. A method was developed to dissociate human ovarian tissue remnants (surplus after tissue cryopreservation) and frozen/thawed ovarian cortex obtained from pre-pubertal and post-pubertal patients. Analyses revealed that age affected the efficacy of dissociation of frozen/thawed ovarian cortical tissue. To detect germ cells in a single cell suspension of ovarian cells, a method was developed for flow cytometry using a monoclonal antibody that recognises the (cytoplasmic) N-terminus region of DDX4. To assess the use of an alternative somatic cell source to support oocyte development, human dermal fibroblasts were aggregated with mouse oocytes and follicle-like structures were formed after 7-day in culture. These findings will contribute to developing the use of the RO using human oocytes and a human somatic cell alternative. The RO method once adapted for human tissue could be used to replace the dysfunctional ovarian somatic cells in POI patients and potentially restore follicle development for pre-pubertal and post-pubertal POI patients.